PROCEDE POUR LE TRAITEMENT DE SCORIES SIDERURGIQUES CONTENANT DES COMPOSES OXYDES DU SODIUM ET DU PHOSPHORE - P. DEMILIE; G. DELLA FAILLE D'HUYSSE (1983)
A slag (5) which is maintained in the molten state is allowed to react with a basic alkaline earth metal compound (6) which is capable of forming a water-insoluble compound with the phosphorus in the slag.